The utility of Jerk-locked back averaging technique in diagnosis of generalized myoclonic epilepsy with normal scalp EEG: A case report. Issue 3 (January 2019) - Zheng, Xiangyu; Wang, Zan; Liu, Chang; Hu, Minghui; Lv, Yudan
Abstract: Rationale: The diagnosis of myoclonic epilepsy and the classification of generalized or partial type may be challenging, especially when the scalp electroencephalogram (EEG) is normal. In such situation, how to apply another electrophysiological technique to begin the diagnosis and classification? The utility of Jerk-locked back averaging technique has been described in our case. Patient concerns: A Chinese patient (male, 21 years old) presented with frequent unilateral or bilateral shoulder-jerking. He has an epilepsy history of complex partial seizure (CPS) or secondary tonic-clonic seizure (sGTCS) for 10 years. Diagnosis: After admission, scalp EEG was performed with the normal result when the patient showed the jerks. According to the patient's clinical presentation, we suspected myolconic seizure, but there was lack of objective evidence. Then we used Jerk-locked back averaging technique to help begin the diagnosis. A bilateral-symmetrical time-locked, evoked cortical averaging potential that preceded the jerk has been found. So the jerks were considered as cortical origin and generalized myoclonic seizure was confirmed. Interventions: So in this situation, we added another antiepileptic drug of Levetiracetam (1500 mg/24 h). Outcomes: One week later, the jerk seizure had disappeared, and in the following visit, he had an improved prognosis with decreased seizure frequency. Lessons: Generalized polyspike-slow wave in EEG was common to see in myoclonic seizure and can help to make the classification. However, it should not dissuade clinicians from the diagnosis of myoclonic epilepsy with normal scalp EEG. Under this condition, we may apply other electrophysiological technique such as Jerk-locked back averaging technique, to give objective evidence to verify the cortical origin.